Migrant remittances can reduce the potential of local forest transitions—a social-ecological regime shift analysis. (13th February 2019) - Ospina, Daniel; Peterson, Garry; Crépin, Anne-Sophie
Abstract: We explore how remittances shape the effect of rural out-migration on the potential for local forest transitions. Building on an existing theoretical model of social-ecological regime shifts that links migration, farmland abandonment, and forest regrowth, we incorporate migrant remittances as an additional rural-urban teleconnection. We also extend the ecological dynamics to include a dynamical forest regrowth rate, generating a slowing-down of regrowth once the landscape has undergone extensive agricultural change. We first analyse how these two extensions to the base model reshape the stability of the system, altering the existence and dynamics of alternative agricultural and forested regimes. Then we explore how two different uses of remittances by rural households (hiring agricultural labor or supplementing household income/consumption) affect the potential for local forest transitions in a context of structural economic change, represented as an increasing differential of rural and urban incomes. We find that remittances change the character of forested and agricultural regimes, and increase the resilience of the agricultural regime. This effect is stronger when remittances are used for hiring labor. The findings are consistent with empirical research that highlights the remarkable persistence of rural livelihoods and landscapes in the face of increasing global connectivity and urbanization. Remittances, and possibly other rural-urban teleconnections, are necessary components for an updated 'economic development pathway' of forest transitions. With this simple model we show that social-ecological regime shifts offer a useful perspective to study land use transition dynamics and advance land change theory.